PELATIHAN BISNIS DIGITAL BAGI INDUSTRI RUMAHAN FURNITURE LOKAL DESA SINDANGMEKAR - Sri Rokhlinasari; Ahmad Sihabuddin; Amaliya Tri Rahmadani; Maria Jamilah; Alya Shafiyah (Bajang Institute, 2025)
Sindangmekar Village holds significant potential in home-based industries, particularly in the production of local furniture rooted in community craftsmanship. However, limited market access and lack of digital technology adoption pose major challenges to business development. This digital business training program aims to enhance the capacity of home industry players by introducing modern business management approaches, especially through the use of digital platforms for marketing, financial management, and brand development. The training employed a participatory approach, including hands-on practice with social media, online marketplaces, and relevant digital content creation. The results indicate an improvement in participants’ understanding and skills in operating digital tools and implementing online marketing strategies. This initiative is expected to serve as a stepping stone toward the digital transformation of local furniture SMEs in Sindangmekar Village, enabling them to compete in broader markets sustainably